PENERAPAN MODEL PEMBELAJARAN TIPE STAD (STUDENT TEAMS ACHIVEMENT DEVISION) PADA MATERI TUMBUHAN HIJAU DALAM MENINGKATKAN HASIL BELAJAR SISWA KELAS V MIN IE LEUBEUE - M. Juned Basyah (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2018)
In teaching and learning activities, one of the main competences and professional skills that must be grasped by educators is the ability of the field of education and teacher training, especially related to learning models. This research is a Classroom Action Research. Data collection is carried out by planning, actiing, observing, and reflecting. Data analysis was carried out descriptively. The results showed that the acquisition of student learning outcomes with the average value in the first cycle of the average value obtained by students was 68.13, the second cycle the average value was 75.42 and the third cycle the average value was 83.75. The percentage of successful students in learning; cycle I: 58.33%, cycle II: 79.17%, and cycle III: 95.83%. Thus it can be concluded, the application of the STAD Cooperative type can improve student learning outcomes, and teachers also improve their skills in using the STAD model. So, the students are encouraged and more enthusiastic to join and understand the Science (IPA) lessons. To develop students' abilities in the science learning process, teachers should use the STAD model so that students are able to understand the material in science learning.